Japonia – nadzór korporacyjny i finanse publiczne - Michalski, Kamil (Gospodarka w Praktyce i Teorii, 2012)
Japan ‒ the third economic power in the world – has been for over a decade, in a state of a prolonged stagnation spreading over the domains of its economy including the banking system. Japan’s participation in the II World War resulted in a humiliating defeat. Japanese cities were completely demolished. Japanese industry and infrastructure were also totally destroyed. Yet, within the next two generations, Japan managed to succeed in economic achievements that were commonly known as “an economic miracle”. The completely ruined country, deprived of any natural resources, has become the world’s economic power, and the leader in many economic domains. The reason for is that Japanese people are characterized by strict obedience towards authorities, diligence, patience and a proper assessment of the post war political situation all over the world made by the Japanese government. Measured and systematic investments of the 60’s and 70’s of the 20th century, were carried out in traditional industries e.g.: metallurgy, textile industry, ship-building industry as well as more modern ones such as automobile and electronics industries. Good quality and reasonable prices of products soon gained popularity among external markets. During a rapid development of 1954-1971, Japan adopted an anti-import policy and closed its market for foreign goods. This policy as well as the well-thought-out strategy of development resulted in a dynamic economic development of the country. Therefore, Japan became an important Americanally in the geopolitical configuration of powers.